Ternary positive electrode material for solid-state lithium battery as well as preparation method and application of ternary positive electrode material
By covering phosphorus on the surface of the nickel-cobalt-manganese ternary precursor, the problems of poor attenuation and thermal stability of the positive electrode material of all solid state lithium battery are solved, and higher cycle stability and battery performance are achieved.
Patent Information
- Application Number
- CN202510086661.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
AI Technical Summary
The nickel, cobalt, manganese ternary cathode material in all-solid lithium batteries has problems of continuous attenuation and poor thermal stability, which limits the cycling and rate performance of the battery.
By coating phosphorus on the surface of the nickel-cobalt-manganese ternary precursor, it resists internal strain, inhibits phase change, and reduces crack generation, thereby improving the cyclic stability of the material.
It significantly improves the cycle stability of the ternary positive electrode material, extends the service life of the battery and improves the performance stability.
Smart Images

Figure CN119898829A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries and relates to a positive electrode material, and in particular to a ternary positive electrode material for solid-state lithium batteries and a preparation method and application thereof. Background Art
[0002] Traditional lithium-ion batteries use liquid electrolytes, which have safety risks such as flammability and leakage. Lithium batteries that use non-flammable, high-temperature-resistant and non-volatile solid electrolytes have the advantages of good safety and a wide operating range, and are expected to gradually replace traditional lithium-ion batteries that use liquid electrolytes.
[0003] The solid-solid interface between the electrode material and the solid electrolyte of all-solid-state lithium-ion batteries has problems such as poor contact, high impedance, and low charging efficiency. High-nickel ternary positive electrode materials have become the most likely common materials for all-solid-state lithium battery positive electrode materials due to their high energy density. However, they have problems such as continuous attenuation and poor thermal stability in all-solid-state lithium batteries, which limits the battery's cycle performance and rate performance. Conventional methods to improve stability include surface coating, element doping, introduction of nanostructures, formation of concentration gradients, and improvement of electrolytes.
[0004] Element doping can significantly improve the electrochemical performance and cycle stability of positive electrode materials, but the doping process will have the risk of over-doping, uniformity problems and cost issues. Nano-sizing can increase the specific surface area of the material, promote the rapid diffusion of lithium ions, and improve the rate discharge performance, but the synthesis conditions are difficult to control. Concentration gradient can improve battery performance and quality, but the preparation process is difficult and the uniformity is difficult to control. Improving the electrolyte has significant advantages in improving the performance of lithium-ion batteries, but it is also accompanied by challenges in cost, compatibility and environment. Surface coating can improve interface performance, prevent dissolution and delithiation, and can also achieve isolation between active materials and electrolytes, and improve specific capacity and cycle performance.
[0005] Therefore, it is necessary to provide a ternary positive electrode material for solid-state lithium batteries that has a simple process and can improve cycle stability, as well as a preparation method and application thereof. Summary of the invention
[0006] In view of the shortcomings of the prior art, the object of the present invention is to provide a ternary positive electrode material for solid-state lithium batteries and a preparation method and application thereof. The preparation method resists the internal strain of the nickel-cobalt-manganese precursor, inhibits further phase change, and reduces the generation of cracks, thereby improving the cycle stability of the ternary positive electrode material.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a ternary positive electrode material for a solid-state lithium battery, the preparation method comprising the following steps:
[0009] The nickel-cobalt-manganese ternary precursor is mixed with an ethanol solution of phosphoric acid, heated until the ethanol is completely evaporated, and then heat-treated in a protective atmosphere; then mixed with a lithium source and calcined; the ternary positive electrode material for a solid-state lithium battery is obtained.
[0010] The present invention resists the internal strain of the nickel-cobalt-manganese precursor by coating the surface of the nickel-cobalt-manganese ternary precursor with phosphorus, inhibits further phase change, reduces the generation of cracks, and thus improves the cycle stability of the ternary positive electrode material.
[0011] Preferably, the phosphoric acid concentration in the phosphoric acid ethanol solution is 0.8 g / L-1.2 g / L;
[0012] Preferably, the solid-to-liquid ratio of the nickel-cobalt-manganese ternary precursor to the ethanol solution of phosphoric acid is 1:10-1:15, and the unit of the solid-to-liquid ratio is g / mL.
[0013] Preferably, the heating is accompanied by stirring.
[0014] Preferably, the heating temperature is 75°C-85°C.
[0015] Preferably, the gas used for the protective atmosphere includes nitrogen and / or an inert gas.
[0016] Preferably, the heat treatment temperature is 480°C-520°C.
[0017] Preferably, the heat treatment time is 280 min-320 min.
[0018] Preferably, the calcination temperature is 800°C-1000°C.
[0019] Preferably, the calcination time is 4h-10h.
[0020] Preferably, the chemical formula of the nickel-cobalt-manganese ternary precursor is Ni 1-x-y Mn x Co y (OH)2, x>0, y>0, 0 <x+y≤0.4。
[0021] Preferably, the preparation method of the nickel-cobalt-manganese ternary precursor comprises the following steps: under stirring conditions, a nickel-cobalt-manganese ternary mixed salt solution, a precipitant solution and a complexing agent solution are mixed in parallel in the base liquid, the feeding is stopped after the co-precipitation reaction reaches the target particle size, and then the reaction is carried out until the materials react completely to obtain the nickel-cobalt-manganese ternary precursor.
[0022] Preferably, the temperature of the base liquid is 40°C-60°C.
[0023] Preferably, the concentration of the complexing agent in the base solution is 4 g / L-8 g / L.
[0024] Preferably, the pH value of the base liquid is 10-12.
[0025] Preferably, the pH value of the coprecipitation reaction is 10-12.
[0026] Preferably, the concentration of the complexing agent in the coprecipitation reaction is 4 g / L-8 g / L.
[0027] Preferably, the coprecipitation reaction temperature is 40°C-60°C.
[0028] In a second aspect, the present invention provides a ternary positive electrode material for a solid-state lithium battery, wherein the ternary positive electrode material for a solid-state lithium battery is prepared by the preparation method described in the first aspect.
[0029] In a third aspect, the present invention provides a solid-state lithium battery, comprising the ternary positive electrode material for a solid-state lithium battery as described in the second aspect.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The present invention resists the internal strain of the nickel-cobalt-manganese precursor by coating the surface of the nickel-cobalt-manganese ternary precursor with phosphorus, inhibits further phase change, reduces the generation of cracks, and thus improves the cycle stability of the ternary positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is the SEM image of the ternary positive electrode material obtained in Example 1. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0034] A certain embodiment of the present invention provides a method for preparing a ternary positive electrode material for a solid-state lithium battery, the preparation method comprising the following steps:
[0035] The nickel-cobalt-manganese ternary precursor is mixed with an ethanol solution of phosphoric acid, heated until the ethanol is completely evaporated, and then heat-treated in a protective atmosphere; then mixed with a lithium source and calcined; the ternary positive electrode material for a solid-state lithium battery is obtained.
[0036] The present invention resists the internal strain of the nickel-cobalt-manganese precursor by coating the surface of the nickel-cobalt-manganese ternary precursor with phosphorus, inhibits further phase change, reduces the generation of cracks, and thus improves the cycle stability of the ternary positive electrode material.
[0037] The lithium source described in the present invention includes but is not limited to lithium hydroxide and / or lithium carbonate; the present invention does not impose too many restrictions on the amount of the lithium source, as long as it can make up for the additional ignition loss during the calcination process.
[0038] In certain embodiments, the concentration of phosphoric acid in the ethanol solution of phosphoric acid is 0.8 g / L-1.2 g / L, for example, 0.8 g / L, 0.9 g / L, 1 g / L, 1.1 g / L or 1.2 g / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0039] In some embodiments, the solid-to-liquid ratio of the nickel-cobalt-manganese ternary precursor to the ethanol solution of phosphoric acid is 1:10-1:15, for example, it can be 1:10, 1:11, 1:12, 1:13, 1:14 or 1:15, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable. The unit of the solid-to-liquid ratio is g / mL.
[0040] In certain embodiments, the heating is accompanied by stirring.
[0041] Stirring during heating is beneficial to the complete evaporation of ethanol and reduces the time required for evaporation of ethanol.
[0042] In some embodiments, the heating temperature is 75°C-85°C, for example, it can be 75°C, 78°C, 80°C, 82°C or 85°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] The present invention does not impose any specific limitation on the heating time, as long as the ethanol can be completely evaporated.
[0044] In some embodiments, the protective atmosphere includes nitrogen and / or an inert gas.
[0045] Optionally, the inert gas includes any one of helium, neon or argon, or a combination of at least two of them. Typical but non-limiting combinations include a combination of helium and neon, a combination of neon and argon, a combination of helium and neon, or a combination of helium, neon and argon.
[0046] In some embodiments, the heat treatment temperature is 480°C-520°C, for example, 480°C, 490°C, 500°C, 510°C or 520°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] In some embodiments, the heat treatment time is 280 min-320 min, for example, 280 min, 290 min, 300 min, 310 min or 320 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] In some embodiments, the calcination temperature is 800°C-1000°C, for example, 800°C, 850°C, 900°C, 950°C or 1000°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0049] In some embodiments, the calcination time is 4 h-10 h, for example, 4 h, 5 h, 6 h, 8 h or 10 h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0050] In certain embodiments, the chemical formula of the nickel-cobalt-manganese ternary precursor is Ni 1-x-y Mn x Co y (OH)2, x>0, y>0, 0 <x+y≤0.4。
[0051] In certain embodiments, the method for preparing the nickel-cobalt-manganese ternary precursor comprises the following steps: under stirring conditions, a nickel-cobalt-manganese ternary mixed salt solution, a precipitant solution and a complexing agent solution are mixed in parallel in a base liquid, feeding is stopped after a co-precipitation reaction to a target particle size, and then reacting until the materials react completely to obtain the nickel-cobalt-manganese ternary precursor.
[0052] In some embodiments, the stirring speed of the stirring condition is 200r / min-400r / min, for example, it can be 200r / min, 250r / min, 300r / min, 350r / min or 400r / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] In some embodiments, the temperature of the base liquid is 40°C-60°C, for example, 40°C, 45°C, 50°C, 55°C or 60°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] In some embodiments, the concentration of the complexing agent in the base solution is 4g / L-8g / L, for example, 4g / L, 5g / L, 6g / L, 7g / L or 8g / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] In some embodiments, the pH value of the base solution is 10-12, for example, it can be 10, 10.5, 11, 11.5 or 12, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0056] In some embodiments, the concentration of the nickel-cobalt-manganese ternary mixed salt solution is 80 g / L-120 g / L, for example, it can be 80 g / L, 90 g / L, 100 g / L, 110 g / L or 120 g / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] In certain embodiments, the nickel salt in the nickel-cobalt-manganese ternary mixed salt solution includes any one of nickel sulfate, nickel nitrate or nickel chloride, or a combination of at least two of them. Typical but non-limiting combinations include a combination of nickel sulfate and nickel nitrate, a combination of nickel nitrate and nickel chloride, a combination of nickel sulfate and nickel chloride, or a combination of nickel sulfate, nickel nitrate and nickel chloride.
[0058] In certain embodiments, the cobalt salt in the cobalt-manganese ternary mixed salt solution includes any one of cobalt sulfate, cobalt nitrate or cobalt chloride, or a combination of at least two of them. Typical but non-limiting combinations include a combination of cobalt sulfate and cobalt nitrate, a combination of cobalt nitrate and cobalt chloride, a combination of cobalt sulfate and cobalt chloride, or a combination of cobalt sulfate, cobalt nitrate and cobalt chloride.
[0059] In certain embodiments, the manganese salt in the manganese-cobalt-manganese ternary mixed salt solution includes any one of manganese sulfate, manganese nitrate or manganese chloride, or a combination of at least two of them. Typical but non-limiting combinations include a combination of manganese sulfate and manganese nitrate, a combination of manganese nitrate and manganese chloride, a combination of manganese sulfate and manganese chloride, or a combination of manganese sulfate, manganese nitrate and manganese chloride.
[0060] In some embodiments, the nickel-cobalt-manganese ternary mixed salt solution is a nickel-cobalt-manganese ternary mixed salt sulfuric acid solution, a nickel-cobalt-manganese ternary mixed salt hydrochloric acid solution, or a nickel-cobalt-manganese ternary mixed salt nitric acid solution.
[0061] In some embodiments, the flow rate at which the nickel-cobalt-manganese ternary mixed salt solution is added to the base liquid in parallel is 6 g / L-10 g / L, for example, it can be 6 g / L, 7 g / L, 8 g / L, 9 g / L or 10 g / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0062] In certain embodiments, the precipitant solution is a sodium hydroxide solution with a mass concentration of 28wt%-32wt%, for example, 28wt%, 29wt%, 30wt%, 31wt% or 32wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0063] In some embodiments, the complexing agent solution is aqueous ammonia with a mass concentration of 10wt%-20wt%, for example, it can be 10wt%, 12wt%, 15wt%, 16wt%, 18wt% or 20wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0064] In certain embodiments, the pH value of the coprecipitation reaction is 10-12, for example, 10, 10.5, 11, 11.5 or 12, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0065] In certain embodiments, the concentration of the complexing agent in the coprecipitation reaction is 4 g / L-8 g / L, for example, 4 g / L, 5 g / L, 6 g / L, 7 g / L or 8 g / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0066] In certain embodiments, the coprecipitation reaction temperature is 40°C-60°C, for example, 40°C, 45°C, 50°C, 55°C or 60°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0067] In some embodiments, the target particle size is a particle size D50 of 3 μm-4 μm, for example, 3 μm, 3.2 μm, 3.5 μm, 3.8 μm or 4 μm, but is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0068] A certain embodiment of the present invention provides a ternary positive electrode material for a solid-state lithium battery, and the ternary positive electrode material for a solid-state lithium battery is prepared by the preparation method described in any embodiment.
[0069] A certain embodiment of the present invention provides a solid-state lithium battery, which includes the ternary positive electrode material for a solid-state lithium battery described in any embodiment.
[0070] Example 1
[0071] This embodiment provides a ternary positive electrode material for a solid-state lithium battery, and the preparation method thereof includes:
[0072] (1) Nickel-cobalt-manganese ternary precursor Ni 0.8 Mn 0.1 Co 0.1 (OH)2 is mixed with an ethanol solution of phosphoric acid and heated at 80°C under stirring until the ethanol is completely evaporated.
[0073] The concentration of phosphoric acid in the ethanol solution of phosphoric acid is 1 g / L; the solid-to-liquid ratio of the nickel-cobalt-manganese ternary precursor to the ethanol solution of phosphoric acid is 1 g:12 mL.
[0074] (2) performing a heat treatment at 500° C. for 300 min in an argon atmosphere; then mixing with lithium carbonate and calcining at 900° C. for 7 h to obtain the ternary positive electrode material LiNi for solid-state lithium batteries. 0.8 Mn 0.1 Co 0.1 (OH)2.
[0075] In this embodiment, the nickel-cobalt-manganese ternary precursor is prepared by the following method:
[0076] Under stirring conditions of 300r / min, a nickel-cobalt-manganese ternary mixed salt solution (a mixed salt solution of nickel sulfate, cobalt sulfate and manganese sulfate, with a total concentration of 100g / L and a flow rate of 8g / L), a sodium hydroxide solution with a mass concentration of 30wt% and ammonia with a mass concentration of 15wt% are mixed in parallel in a base liquid (temperature of 50°C, ammonia concentration of 6g / L, and pH value of 11), and a coprecipitation reaction is carried out until the target particle size D50 reaches 3μm, the feeding is stopped, and then the reaction is carried out until the materials are completely reacted to obtain the nickel-cobalt-manganese ternary precursor; a high-efficiency concentrator is used during the coprecipitation reaction.
[0077] Example 2
[0078] This embodiment provides a ternary positive electrode material for a solid-state lithium battery, and the preparation method thereof includes:
[0079] (1) Nickel-cobalt-manganese ternary precursor Ni 0.8 Mn 0.1 Co 0.1 (OH)2 is mixed with an ethanol solution of phosphoric acid and heated at 75°C under stirring until the ethanol is completely evaporated.
[0080] The concentration of phosphoric acid in the ethanol solution of phosphoric acid is 0.8 g / L; the solid-to-liquid ratio of the nickel-cobalt-manganese ternary precursor to the ethanol solution of phosphoric acid is 1 g:10 mL.
[0081] (2) performing a heat treatment at 480° C. for 320 min in an argon atmosphere; then mixing with lithium carbonate and calcining at 800° C. for 10 h to obtain the ternary positive electrode material LiNi for solid-state lithium batteries. 0.8 Mn 0.1 Co 0.1 (OH)2.
[0082] In this embodiment, the nickel-cobalt-manganese ternary precursor is prepared by the following method:
[0083] Under stirring conditions of 200r / min, a nickel-cobalt-manganese ternary mixed salt solution (a mixed salt solution of nickel sulfate, cobalt sulfate and manganese sulfate, with a total concentration of 80g / L and a flow rate of 6g / L), a sodium hydroxide solution with a mass concentration of 28wt% and ammonia with a mass concentration of 10wt% are mixed in parallel in a base liquid (temperature of 40°C, ammonia concentration of 4g / L, and pH value of 10), and a coprecipitation reaction is carried out until the target particle size D50 reaches 3μm, the feeding is stopped, and then the reaction is carried out until the materials are completely reacted to obtain the nickel-cobalt-manganese ternary precursor; a high-efficiency concentrator is used during the coprecipitation reaction.
[0084] Example 3
[0085] This embodiment provides a ternary positive electrode material for a solid-state lithium battery, and the preparation method thereof includes:
[0086] (1) Nickel-cobalt-manganese ternary precursor Ni 0.8 Mn 0.1 Co 0.1 (OH)2 is mixed with an ethanol solution of phosphoric acid and heated at 85°C under stirring until the ethanol is completely evaporated.
[0087] The concentration of phosphoric acid in the ethanol solution of phosphoric acid is 1.2 g / L; the solid-to-liquid ratio of the nickel-cobalt-manganese ternary precursor to the ethanol solution of phosphoric acid is 1 g:15 mL.
[0088] (2) performing a heat treatment at 520° C. for 280 min in an argon atmosphere; then mixing with lithium carbonate and calcining at 1000° C. for 4 h to obtain the ternary positive electrode material LiNi for solid-state lithium batteries. 0.8 Mn 0.1 Co 0.1 (OH)2.
[0089] In this embodiment, the nickel-cobalt-manganese ternary precursor is prepared by the following method:
[0090] Under stirring conditions of 400r / min, a nickel-cobalt-manganese ternary mixed salt solution (a mixed salt solution of nickel sulfate, cobalt sulfate and manganese sulfate, with a total concentration of 120g / L and a flow rate of 10g / L), a sodium hydroxide solution with a mass concentration of 32wt% and ammonia with a mass concentration of 20wt% are mixed in parallel in a base liquid (temperature of 60°C, ammonia concentration of 8g / L, and pH value of 12), and a coprecipitation reaction is carried out until the target particle size D50 reaches 4μm, the feeding is stopped, and then the reaction is carried out until the materials are completely reacted to obtain the nickel-cobalt-manganese ternary precursor; a high-efficiency concentrator is used during the coprecipitation reaction.
[0091] Example 4
[0092] This embodiment provides a ternary positive electrode material for a solid-state lithium battery, which is the same as that of Embodiment 1 except that the concentration of phosphoric acid in the ethanol solution of phosphoric acid is 0.5 g / L.
[0093] Example 5
[0094] This embodiment provides a ternary positive electrode material for a solid-state lithium battery, which is the same as that of Embodiment 1 except that the concentration of phosphoric acid in the ethanol solution of phosphoric acid is 1.5 g / L.
[0095] Example 6
[0096] This embodiment provides a ternary positive electrode material for a solid-state lithium battery, which is the same as that of Embodiment 1 except that the heat treatment temperature is 450°C.
[0097] Example 7
[0098] This embodiment provides a ternary positive electrode material for a solid-state lithium battery, which is the same as that of Embodiment 1 except that the heat treatment temperature is 540°C.
[0099] Comparative Example 1
[0100] This comparative example provides a ternary positive electrode material for a solid-state lithium battery, and the preparation method thereof comprises:
[0101] (1) Nickel-cobalt-manganese ternary precursor Ni 0.8 Mn 0.1 Co 0.1 (OH)2 is mixed with an aqueous solution of phosphoric acid and heated at 80°C under stirring until the water is completely evaporated.
[0102] The concentration of phosphoric acid in the aqueous solution of phosphoric acid is 1 g / L; the solid-to-liquid ratio of the nickel-cobalt-manganese ternary precursor to the aqueous solution of phosphoric acid is 1 g:12 mL.
[0103] (2) performing a heat treatment at 500° C. for 300 min in an argon atmosphere; then mixing with lithium carbonate and calcining at 900° C. for 7 h to obtain the ternary positive electrode material LiNi for solid-state lithium batteries. 0.8 Mn 0.1 Co 0.1 (OH)2.
[0104] The preparation method of the nickel-cobalt-manganese ternary precursor in this comparative example is the same as that in Example 1.
[0105] Performance Characterization
[0106] Solid-state batteries were assembled using the ternary cathode materials provided in the above embodiments and comparative examples. First, 200 mg of sulfide-based electrolyte powder was placed inside a solid-state battery mold and cold-pressed at a pressure of 220 MPa for 10 min to obtain a dense electrolyte sheet.
[0107] The ternary cathode material and sulfide-based electrolyte powder were weighed in a mass ratio of 8:2 and manually mixed in an agate mortar to obtain a composite cathode material; the composite cathode material was evenly spread on one side of the electrolyte layer, and pressurized to make the cathode layer in close contact with the electrolyte sheet; finally, the lithium-indium alloy was placed on the other side of the electrolyte sheet. A stainless steel shell was used to control the working pressure of the solid-state battery, which was 120 MPa.
[0108] The preparation method of sulfide-based electrolyte powder is as follows: in an argon atmosphere, Li2S, P2S2, SiS2 and LiCl are added into a zirconia ball mill in a molar ratio of 55:30:10:5, the diameter of the zirconia ball is 10 mm, the ball mill speed is 370 r / min, and the ball milling time is 40 h; the powder obtained by ball milling is transferred to a quartz tube and annealed at 475°C for 8 h to obtain a sulfide-based electrolyte.
[0109] The initial discharge specific capacity and cycle stability of the obtained solid-state battery were tested. The test method was to use a constant current charge and discharge tester to test the initial discharge specific capacity and cycle stability of the solid-state battery respectively. The voltage range of the cycle test was 2.8-4.3V, 0.1C (1C = 180mA / g) was pre-activated for 3 cycles, and then cycled at 0.3C for 100 cycles. The results are shown in Table 1.
[0110] Table 1
[0111] Initial discharge specific capacity (mAh / g) Cycle capacity retention rate (%) Example 1 252 94.54 Example 2 224 93.97 Example 3 235 94.13 Example 4 209 92.89 Example 5 217 93.36 Example 6 238 93.17 Example 7 232 93.54 Comparative Example 1 191 90.51
[0112] In summary, the present invention resists the internal strain of the nickel-cobalt-manganese precursor, inhibits further phase change, reduces the generation of cracks, and thus improves the cycle stability of the ternary positive electrode material by coating the surface of the nickel-cobalt-manganese precursor with phosphorus.
[0113] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a ternary positive electrode material for a solid-state lithium battery, characterized in that: The preparation method comprises the following steps: The nickel-cobalt-manganese ternary precursor is mixed with an ethanol solution of phosphoric acid, heated until the ethanol is completely evaporated, and then heat-treated in a protective atmosphere; then mixed with a lithium source and calcined; the ternary positive electrode material for a solid-state lithium battery is obtained.
2. The preparation method according to claim 1, characterized in that: The phosphoric acid concentration in the phosphoric acid ethanol solution is 0.8 g / L-1.2 g / L; And / or, the solid-to-liquid ratio of the nickel-cobalt-manganese ternary precursor to the ethanol solution of phosphoric acid is 1:10-1:15, and the unit of the solid-to-liquid ratio is g / mL.
3. The preparation method according to claim 1 or 2, characterized in that: The heating is accompanied by stirring; And / or, the heating temperature is 75°C-85°C.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The gas used in the protective atmosphere includes nitrogen and / or inert gas; And / or, the temperature of the heat treatment is 480°C-520°C; And / or, the heat treatment time is 280min-320min.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The calcination temperature is 800°C-1000°C; And / or, the calcination time is 4h-10h; And / or, the chemical formula of the nickel-cobalt-manganese ternary precursor is Ni 1-x-y Mn x Co y (OH)2, x>0, y>0, 0 <x+y≤0.4。 6. The preparation method according to any one of claims 1 to 5, characterized in that: The preparation method of the nickel-cobalt-manganese ternary precursor comprises the following steps: Under stirring conditions, the nickel-cobalt-manganese ternary mixed salt solution, the precipitant solution and the complexing agent solution are mixed in parallel in the bottom liquid, and the feeding is stopped after the coprecipitation reaction reaches the target particle size, and then the reaction is continued until the materials react completely to obtain the nickel-cobalt-manganese ternary precursor.
7. The preparation method according to claim 6, characterized in that: The temperature of the base liquid is 40°C-60°C; and / or, the concentration of the complexing agent in the base solution is 4 g / L-8 g / L; And / or, the pH value of the base liquid is 10-12.
8. The preparation method according to claim 6, characterized in that: The pH value of the coprecipitation reaction is 10-12; And / or, the concentration of the complexing agent in the coprecipitation reaction is 4 g / L-8 g / L; And / or, the temperature of the coprecipitation reaction is 40°C-60°C.
9. A ternary positive electrode material for a solid-state lithium battery, characterized in that: The ternary positive electrode material for solid-state lithium batteries is prepared by the preparation method described in any one of claims 1 to 8.
10. A solid-state lithium battery, characterized in that: The solid-state lithium battery comprises the ternary positive electrode material for a solid-state lithium battery as described in claim 9.